Description of two new idiocerine leafhoppers of the genus Chinaocerus (Hemiptera: Cicadellidae) from southwestern China - Zhang, Bin; Chi, Wenfeng; Webb, M.d. (Zootaxa, 2018)
The leafhopper genus Chinaocerus Zhang & Li (Cicadellidae: Idiocerinae) currently includes three species, C. bispinatus Zhang & Li (type species), C. kangdingensis Zhang & Li and C. shii Zhang & Li from southwestern China. Two new species, C. tubulatus Zhang & Webb sp. nov. and C. sexspinosus Zhang & Webb sp. nov. from Yunnan Province, China, are here described and a checklist and key to species are provided.